The Evolution of Thematic and Integrative Approaches in Social Studies Education: A Historical and Conceptual Analysis - Eka Yuliana Rahman; Nana Supriatna; Juju Masunah; Erlina Wiyanarti; Nur Allan Lasido; Moh Fikri Pomalingo (Jurnal Ilmiah Iqra', 2025)
This article examines thematic and integrated approaches in Social Studies Education through ontological, epistemological, and axiological perspectives. It arises from the limited availability of studies that explore these approaches from historical and developmental perspectives. The purpose of this literature research is to describe the early evolution of thematic and integrated approaches and to explain how educational practices have changed over time. Using the library research method by Both and Williams (2016), the study follows ten stages of data collection, analysis, and reduction based on relevant references. Through the Publish or Perish application, 30 relevant articles were identified using the keywords "pendekatan tematik dan terpadu." The findings reveal that interdisciplinary contexts provide a crucial perspective in Social Studies, emphasizing integration among disciplines as a core principle. These approaches gained prominence in the 20th century, influenced by Bruner's constructivism (1960) and Krathwohl's revision of Bloom's Taxonomy (2002). Models developed by Fogarty (1991) and Jacobs & Borland (1986) demonstrate their practical application, with Indonesian curricula applying integrated, correlated, and separated models across different education levels